Factors that creates customer awareness on the promotion strategies made by Melaka Stadium Corporation / Jihan Ayuni Abdul Rahim - Abdul Rahim, Jihan Ayuni (Faculty of Business and Management, 2008)
Malacca Stadium Corporation was established with the main objectives of marketing the Sport Event and offers other services for local and international. Its main function is to provide goods and quality services to enhance their customers' satisfaction with their company's motto which is "Your Satisfaction is Our Priority". The main objective of this research is to study on "Factors that creates customer awareness on the Promotions Strategies Made By Melaka Stadium Corporation". Further, it is to know whether customers' are aware or not with the promotions activities made by Malacca Stadium Corporation.